2021
DOI: 10.30813/jbam.v14i2.2795
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Effect of Motivation and Job Satisfaction Between Work Environment and the Performance of Judges and Court Clerks in Riau Islands Province

Abstract: The objective of this research is to distinguish the effect of work environment on the performance of judges and court clerks in the Riau Islands Province of Indonesia, and the impact of motivation and job satisfaction as intervening variables in influencing the model. A census questionnaire was produced and validated employing a pilot data. A total of 109 questionnaires were distributed to judges and court clerks in Riau Island Province and all questionnaires were returned and validated. Regression was utilis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
0
0
1
Order By: Relevance
“…The results of this study are supported by research by Yasa, et al (2017), which found work motivation has an effect on increasing employee performance. This finding is supported by the research of Indah & Riana (2020) and Nurdiansyah et al (2020) who found a relationship between motivation and employee performance which is mediated by job satisfaction providing an increase in employee performance and Tan & Sudhartio (2021) found that motivation has a positive and significant effect on job satisfaction. Motivation has a positive and significant effect on employee performance mediated by job satisfaction from research by Richar et al The better work motivation, employee performance will also increase.…”
Section: The Relationship Between Employee Motivation and Performance...supporting
confidence: 70%
“…The results of this study are supported by research by Yasa, et al (2017), which found work motivation has an effect on increasing employee performance. This finding is supported by the research of Indah & Riana (2020) and Nurdiansyah et al (2020) who found a relationship between motivation and employee performance which is mediated by job satisfaction providing an increase in employee performance and Tan & Sudhartio (2021) found that motivation has a positive and significant effect on job satisfaction. Motivation has a positive and significant effect on employee performance mediated by job satisfaction from research by Richar et al The better work motivation, employee performance will also increase.…”
Section: The Relationship Between Employee Motivation and Performance...supporting
confidence: 70%
“…Artinya lingkungan kerja berpengaruh positif dan signifikan terhadap motivasi kerja, apabila kondisi lingkungan kerja mengalami peningkatan maka dapat meningkatkan motivasi kerja karyawan PT Bali Food Lestari Badung, sehingga hipotesis kedua dapat diterima. Hal ini sejalan oleh hasil dari penelitian Antony & Hariyanto (2021), Budiono et al (2021), Jasmine & Edalmen (2020), Laras et al (2021), Tan & Sudhartio (2021) dan Yani (2021) yang menyatakan bahwa lingkungan kerja berpengaruh positif dan signifikan terhadap motivasi kerja. Lingkungan kerja memberikan pengaruh positif terhadap motivasi kerja dimana semakin baik lingkungan kerja akan meningkatkan motivasi kerja karyawannya (Laras et al, 2021).…”
Section: Gambar 2 Model Analisis Jalurunclassified